Optimization of Aging Time and Temperature for Four Malaysian Rice Cultivars - Faruq, Golam; Mohamad, O.; Hadzim, M.; Meisner, C.A. (Pakistan Journal of Nutrition, 2003)
Aging is a process that can develop rice-cooking quality. Specially, it helps to increase kernel elongation rate during cooking time. We have aged four popular Malaysian rice cultivars in different time and temperature conditions and we have observed that maximum good kernel elongation ratio for Mahsuri and Mahsuri Mutant are 100 °C for 5 hours. In 9192, maximum kernel elongation ratio was observed at 110 °C with 5 hours and for putri it was 110 °C for 3 hours. In Mahsuri, proportionate change range was 0.03 to 0.23. So we can say that the degree of elongation of Mahsuri is poor to low. For Mahsuri Mutant proportionate change range was 0.33 to 0.65 and the degree of elongation Mahsuri Mutant can be graded grading as medium. Proportionate change range was observed 0.23 to 0.60 in 9192 and it is convenient to say that degree of elongation of 9192 is low to medium. Finally, in putri a very interesting observation was occurred. When it was treated at 90 °C the lowest proportionate change (0.40) was observed with 1 hour curing and highest (0.55) was with 3 hours curing. In 100 °C, maximum proportionate changed was observed (0.59) with 3 hours curing and lowest was observed (0.41) at 7 hours curing. At 110 °C, lowest proportionate change (0.75) was observed with 9 hours curing and maximum proportionate change was observed with 7 hours curing (0.90). So we can see at 90 and 100 °C with different curing time proportionate changes was in between 0.40 to 0.59 and the degree of elongation may consider as medium. But at 110 °C temperature we were surprised and observed that with all different temperatures the degree of elongation was high (Range 0.75-0.90). At this temperature (110 °C) Putri showed good kernel elongation ratio and high degree of elongation like the other Basmati type fine rice. Higher actual elongation is a desirable character for the consumers; the following results are the average of different curing time because our used grain size was not truly uniform (Mahsuri 5.0 mm - 5.5 mm, Mahsuri Mutant 6.2 mm - 6.75 mm, 9192 6.5 mm - 7.0 mm and Putri 6.5 mm - 7.0 mm). In this experiment we have also observed that variety, temperature and time significantly influence elongation ratio, Proportionate change and actual elongation. Variety time interaction, variety temperature interaction and variety temperature time interactions also significantly influenced these physical properties of rice kernel. Temperature time interaction does not significantly influence on elongation ratio, but this interaction influence proportionate change and actual elongation.